Volatile fingerprints and biomarkers of three representative kiwifruit cultivars obtained by headspace solid-phase microextraction gas chromatography mass spectrometry and chemometrics. (15th January 2019) - Zhang, Chun-Yun; Zhang, Qiong; Zhong, Cai-Hong; Guo, Ming-Quan
Highlights: Volatile fingerprints of three kiwifruit cultivars have been analyzed using HS-SPME-GC-MS. Multivariate analysis was used to differentiate the volatiles in different cultivars. Six compounds have been identified as maturity-independent biomarkers for kiwifruit cultivars. Abstract: Volatile aroma of kiwifruit is a mixture of complicated and time-dependent compounds, and thereby the study of these compounds required distinguished analytical techniques as well as robust data analysis techniques. In this work, we report on the volatile fingerprints and biomarkers of three representative kiwifruit cultivars with commercial importance using headspace solid-phase microextraction gas chromatography-mass spectrometric (HS-SPME-GC-MS) coupled with multivariate analysis. As a result, 95 volatiles have been analyzed from the fingerprints, and ultimately six of which were identified as volatile biomarkers of the kiwifruit cultivars studied, which are formic acid octyl ester, 2-Methylbicyclo[4.3.0]non-1(6)-ene, 1-ethoxy-2, 4-hexadiene, and 2-methyl-5-(1-methylethyl)-bicyclo[3.1.0]hex-2-ene for Jintao ( A. chinensis ), and 1-methoxy-2-methyl-benzene and (E, E)-2, 4-heptadienal for Cuiyu ( A. deliciosa ), respectively. Since the samples of each cultivar were in various maturities, these compounds could be taken as the maturity-independent volatile biomarkers for the kiwifruit cultivars, which would be valuable for marker-assisted flavour breeding in the kiwifruit production.